Anthelmintic Activity of Tomato Leaf Extract - Sravanthi, Srilakshmi Sidagonde, Sarvani Manthri*, Kota Chaitanya (Journal of Phytology, 2011)
The aim of the present study was to investigate theÃ‚Â anthelminticÃ‚Â activity ofÃ‚Â tomato (Solanum lycopersicum) leaf extract using adult earthworm, PheritimaÃ‚Â posthuma. The methanolicÃ‚Â extract of the crude drug of different concentrations were tested which involve determination of paralysis time and death time.Ã‚Â Albendazole is used as standard and it was found that the methanolicÃ‚Â extract of the tomato leaves showed a better anthelminthic activity in comparison with the standard. Key words: AnthelminticÃ‚Â activity,Ã‚Â Albendazole, Earthworm, Tomato <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Sarvani Manthri et al. AnthelminticÃ‚Â Activity of Tomato Leaf Extract. J Phytol 3/3 (2011) 15-17.